PAVING BLOCK STRENGTH ANALYSIS OF REINFORCD PAVING BLOCK USING WIRE HARMONIKA - Syaputra, Eddy Erawan; ., Sazuatmo; Wardhana, Fenty Wisnu (Jurnal Ilmiah Teknik Sipil; Vol 26 No 2 (2022): Jurnal Ilmiah Teknik Sipil, Vol. 26 No. 2, Juli 2022, 2022)
Paving block is one of the building materials used as the top layer of the road structure other than asphalt and concrete. Nowadays, many choose paving blocks to be used in park areas, pedestrians/ walks, yard, parking lots and so on. This study aims to determine the value of compressive strength and water absorption after adding reinfocement using harmonica wire as much as 0, 1, 2, and 3 layers. The method used is the compressive strength and water absorption test method in the laboratory using the MATEST digital compresive strength test machine (CYBER-PLUS EVOLUTION), and the water absorptionn test equipment using an oven for drying the specimens after immersion. The results of this study indicate that the paving block added with 0 layers of harmonica wire resulted in a comressive strength test value of 204,06 kg/cm² and a water absorption capacity of 7,7%, the addition of 1 layer resulted in a compressive strength test value of 252,98 kg/cm² and 5,9% water absorption, the addition of 2 layers resulted in a compressive strength test value of 278,05 kg/cm² and a water absorption capacity of 5,1%, the addition of 3 layers resulted in a compressive strength test value of 297,84 kg/cm² and water absorption 4,2%. The addition of 1, 2, dan 3 layers of harmonica wire can be used for paving block reinforcement, because it can improve the quality of the paving block